An All-in-One Adhesive Does Not Etch beyond Hybrid Layers - Kim, J. (SAGE Publications, 2010)
Continuous etching of aggressive all-in-one adhesives occurs in wet dentin tubules after polymerization of the adhesives. This study challenged the hypothesis that unpolymerized acidic monomers from an aggressive all-in-one self-etching adhesive continue to etch beyond dentin hybrid layers. Dentin surfaces bonded with Adper Prompt L-Pop were sectioned into 0.3-mm-thick slabs. Some of the slabs were stored in water (pH 6.8) or glycine buffer (pH 11.1) for six weeks and then examined by CLSM, SEM, and TEM. The rest were immersed in a biomimetic remineralizing medium for up to 4 months. Morphologic analysis indicated no difference in demineralization thickness between the two 6-week storage groups. However, increased permeability and loss of integrity occurred along the base of the hybrid layers in the glycine buffer group, but not in the water storage group. These findings were also confirmed by the results of biomimetic remineralization along the bases of those hybrid layers.